Natural and engineered solutions for drinking water supplies lessons from the Northeastern United States and directions for global watershed management - Alcott, Emily; Ashton, Mark S.; Gentry, Bradford S. (Taylor & Francis, 2013)
"Watershed planning is important for expanding cities in the developing world. Outlining proven approaches for a secure drinking water supply anywhere, this book focuses on the history, current conditions, and future of drinking water supplies for cities in the northeastern United States. Chapters examine how, when, and where it makes environmental, economic, and social sense to protect and manage upland forests to produce water as a downstream service. Using city watershed case studies, the text demonstrates that such stewardship is far more preferable than developing land and using engineering, technology, and artificial filtration as a solution to maintaining clean drinking water"-- Provided by publisher.
Keywords: Watershed management -- Northeastern States.; Drinking water -- Purification -- Cost effectiveness.; Wellhead protection -- Northeastern States.; elektronické knihy; electronic books